Leucine-rich repeat kinase 2 regulates autophagy through a calcium-dependent pathway involving NAADP. - Gómez-Suaga, P; Luzón-Toro, B; Churamani, D; Zhang, L; Bloor-Young, D; Patel, S; Woodman, P; Churchill, G; Hilfiker, S (2012)
Mutations in the leucine-rich repeat kinase-2 (LRRK2) gene cause late-onset Parkinson's disease, but its physiological function has remained largely unknown. Here we report that LRRK2 activates a calcium-dependent protein kinase kinase-β (CaMKK-β)/adenosine monophosphate (AMP)-activated protein kinase (AMPK) pathway which is followed by a persistent increase in autophagosome formation. Simultaneously, LRKR2 overexpression increases the levels of the autophagy receptor p62 in a protein synthesis-dependent manner, and decreases the number of acidic lysosomes. The LRRK2-mediated effects result in increased sensitivity of cells to stressors associated with abnormal protein degradation. These effects can be mimicked by the lysosomal Ca(2+)-mobilizing messenger nicotinic acid adenine dinucleotide phosphate (NAADP) and can be reverted by an NAADP receptor antagonist or expression of dominant-negative receptor constructs. Collectively, our data indicate a molecular mechanism for LRRK2 deregulation of autophagy and reveal previously unidentified therapeutic targets.